CT-guided radiofrequency ablation of the extracranial cranial nerve for the treatment of Meige’s syndrome - Huang, Bing; Du, Xin-dan; Yao, Ming; Lin, Hui-dan; Yu, Wen-hua; Zhou, Qing-he (Frontiers in Neuroscience, 2022)
Background Meige’ s syndrome, a rare form of dystonia, lacks effective treatment. The purpose of this study was to determine the effects of CT-guided percutaneous extracranial radiofrequency ablation of the facial and/or trigeminal nerves in the treatment of Meige’s syndrome. Methods A total of 10 patients were enrolled in this study, with the numbers of blepharospasm dystonia syndrome (BDS), oromandibular dystonia syndrome (ODS), and blepharospasm combined with oromandibular dystonia syndrome (B-ODS) being 7, 1, and 2, respectively. BDS patients underwent radiofrequency ablation of the bilateral stylomastoid foramen facial nerve; ODS patients underwent radiofrequency ablation of the bilateral foramen oval trigeminal mandibular branch, and B-ODS patients underwent radiofrequency ablation of the bilateral stylomastoid foramen facial nerve and foramen oval trigeminal mandibular branch. The therapeutic effects and complications were observed. Results All 10 patients in this series experienced improved Meige’s syndrome-related symptoms after extracranial radiofrequency ablation of the cranial and/or mandibular branches of the extracranial trigeminal nerve. Adverse events included class II–III facial paralysis and/or mandibular skin numbness. Two patients had recurrences at the 18th and 22nd months postoperatively, respectively; the other patients were being followed up. Conclusion These results shown that CT-guided radiofrequency ablation of bilateral stylomastoid foramen facial nerve and/or oval foramen trigeminal mandibular branch can effectively treat the corresponding types of Meige’s syndrome. According to preliminary observations, the therapeutic effect may last more than 18 months.